Size Does Not Make the Difference: 3D/4D Transperineal Sonographic Measurements of the Female Urethra in the Assessment of Urinary Incontinence Subtypes. (21st November 2016) - Kupec, Tomas; Pecks, Ulrich; Gräf, Charlotte M.; Stickeler, Elmar; Meinhold-Heerlein, Ivo; Najjari, Laila
Abstract : Purpose. The objective was to evaluate the usefulness of transperineal ultrasound in the assessment of the urethral length and urethral lumen by 3D/4D transperineal sonography to discriminate between female patients with subtypes of urinary incontinence. Methods. A total of 150 female patients underwent an examination because of urinary incontinence. 41 patients were diagnosed with urgency urinary incontinence (OAB), 67 patients were diagnosed with stress urinary incontinence (SUI), and 42 patients were in the control group (CTRL). Three diameters of the urethral lumen (proximal (U1), medial (U2), and distal (U3)) and the urethral length were measured. By the assessment of the urethral lumen, the presence of the urethral funneling was evaluated. Results. We found a significant difference in the urethral length and urethral lumen U2 of OAB and SUI versus CTRL. The urethral length was significantly greater (P < 0 . 05 ) and the urethral lumen was significantly wider (P < 0 . 05 ) in the patients with urinary incontinence. The incidence of the urethral funneling was significantly higher (P < 0 . 05 ) in the study groups with urinary incontinence than in the control group. Conclusions. Our results have shown the urethral changes obtained by ultrasound in patients with urinary incontinence, but they are still insufficient to distinguish between subtypes of urinary incontinence.